Forecasting oilseeds prices in India: Case of groundnut: FORECASTING OILSEEDS PRICES IN INDIA: CASE OF GROUNDNUT - ASHWINI DAREKAR; A AMARENDER REDDY (Journal of Oilseeds Research, 2017)
Oilseed crops contribute 13 per cent of the country’s gross cropped area and 10 per cent of the value of all agricultural produce. Groundnut is the major oilseed crop accounting about 30 per cent of the total oilseeds cropped area in the country with a production share of about 36 per cent. Prices of groundnuts are highly volatile, hence farmers need a reasonable forecasting of harvest period price to decide on the acreage under groundnut. Hence, the present study aimed to build a model to forecast the groundnut prices and applied to forecast kharif harvesting season prices in major producing states viz., Gujarat, Andhra Pradesh, Tamil Nadu, Karnataka and Maharashtra. The prices were forecasted by using the time series data of monthly average prices for the period of 11 years (January 2006 to December 2016). ARIMAmodel introduced byBox and Jenkins (1970) which is the most widely used amongst time series models was used for predictions. R2, RMSE, MAPE, MAE and normalized BIC these parameters were used to test the reliability ofmodel. Model parameters were estimated by using the Statistical Packages for Social Sciences software. In India kharif season groundnut is harvested during the period of September to December. Forecast shows that market prices of groundnut, would be ruling in the range of ` 3,760 to 5,520 per quintal in kharif harvesting season (2017-18). Hence, using ARIMA model to forecast groundnut prices is very useful not only to farmers but in policy formulation and also in promoting efficiency of groundnut marketing. The farmers are advised to take marketing decision accordingly.